New therapeutic options for treating type-2 diabetes: a review of insulin analogs and premixed insulin analogs. - Choe, Charles (National Medical Association, 2007)
There is a growing consensus that blood glucose control, and postprandial control in particular, must become more aggressive if we are to stem the growing tide of diabetes-related complications and mortality. For most patients, this means that insulin therapy must begin earlier and that insulin must be titrated sufficiently to achieve tighter glycemic targets. The limitations of traditional treatment regimens, delivery devices and conventional insulin formulations, in conjunction with patient factors, have prevented the majority of people with type-2 diabetes from realizing the potential benefits of insulin therapy and achieving recommended glycemic targets. Fortunately, modern insulin analog formulations, new treatment regimens, and advanced delivery devices are now available. This review will discuss features of these new tools, and compare the benefits of using premixed insulin versus a basal-only approach to initiating insulin therapy. Once physicians become familiar with these tools and incorporate them into daily practice, they will be able to better tailor diabetes self-management programs to the needs of individual patients. The result will be that more patients should be able to reach recommended glycemic targets with greater convenience and safety than has previously been available.